1981
DOI: 10.1159/000158334
|View full text |Cite
|
Sign up to set email alerts
|

Receptors for 5-Hydroxytryptamine in Rabbit Isolated Ear Artery and Aorta

Abstract: The effects of N, N’-bis-(O-methoxybenzylaminohexyl)-cystamine tetrahydrochloride (BHC), 2-brom-d-lysergic acid diethylamide (BOL) and prazosin on 5-hydroxytryptamine (5-HT) dose-response curves in rabbit ear artery and thoracic aorta were determined. BHC, an irreversible alpha-adrenoceptor antagonist, and prazosin had no substantial effect while BOL shifted the 5-HT dose-response curve to the right in aorta. BHC shifted the curve to the right and reduced maximal response to 5-HT in ear artery. BOL shifted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Although both a-adrenergjc and serotonergic receptors exist on the smooth muscle plasmalemma of rabbit aorta, 5-HT is thought to stimulate only serotonergic receptors in this artery (Apperiey et al, 1976;Purdy et al, 1981). To determine the extent to which 5-HT contractions in RTA are dependent on the presence of extracellular calcium, vascular rings cut from rabbit aortas were stimulated with a maximal concentration of 5-HT (see Table 2) in a calcium-containing or a calcium-free solution in a manner analogous to rings of BVCA.…”
Section: Rabbit Thoracic Aortamentioning
confidence: 99%
See 1 more Smart Citation
“…Although both a-adrenergjc and serotonergic receptors exist on the smooth muscle plasmalemma of rabbit aorta, 5-HT is thought to stimulate only serotonergic receptors in this artery (Apperiey et al, 1976;Purdy et al, 1981). To determine the extent to which 5-HT contractions in RTA are dependent on the presence of extracellular calcium, vascular rings cut from rabbit aortas were stimulated with a maximal concentration of 5-HT (see Table 2) in a calcium-containing or a calcium-free solution in a manner analogous to rings of BVCA.…”
Section: Rabbit Thoracic Aortamentioning
confidence: 99%
“…In those vessels that do contract to 5-HT, contraction is either monophasic (tension increases rapidly to a maximum and remains essentially sustained, (Nielsen and Owman, 1971;Towart, 1981), biphasic (tension decreases transiently after the initial rapid contraction, (Steinsland et al, 1973;Towart, 1981), or transient (Silverberg et al, 1979) depending on vessel type. Such heterogeneity of response is not understood, but may be attributed to a variation in receptor number (Black et al, 1981) or in specificity of receptor binding throughout different vasculatures (Purdy et al, 1981), or to the existence in discrete vasculatures of receptor-response coupling that is not homogenous (Ratz and Flaim, 1982).…”
mentioning
confidence: 99%
“…There is a considerable amount of data available about interactions between the adrenergic and serotonergic receptors in isolated blood vessels [21][22][23]. It was reported that in the rabbit aorta, 5-HT and NA might combine with different receptors but that in the ear artery they appeared to combine with the same receptor [23].…”
Section: Discussionmentioning
confidence: 99%
“…We have provided a number of examples that contraction per se caused a subsequent increased responsiveness to other agonists. However, there is considerable evi dence that 5-HT acts at a-adrenoceptors in the ear artery [ 1,12,13,20]. Therefore 5-HT may have actually desensitized the a-adrenoceptors (and NE desensitized the 5-HT recep tor) resulting in decreased responsiveness.…”
Section: Discussionmentioning
confidence: 99%